The impact of cold spells on mortality from a wide spectrum of diseases in Guangzhou, China. (13th January 2021) - Chen, Jinjian; Dong, Hang; Yang, Jun; Li, Li; Jin, Jieqi; Yang, Zhou; Lin, Guozhen; Ou, Chun-Quan
Abstract: Cold spells have been associated with mortality from a few broad categories of diseases or specific diseases. However, there is a lack of data about the health effects of cold spells on mortality from a wide spectrum of plausible diseases which can reveal a more comprehensive contour of the mortality burden of cold spells. We collected daily mortality data in Guangzhou during 2010–2018 from the Guangzhou Center for Disease Control and Prevention. The quasi-Poisson generalized linear regression model mixed with the distributed lag non-linear model (DLNM) was conducted to examine the health impacts of cold spells for 11 broad causes of death groupings and from 35 subcategories in Guangzhou. Then, we examined the effect modification by age group (0–64 and 65+ years) and sex. Effects of cold spells on mortality generally delayed for 3–5 d and persisted up to 27 d. Cold spells were significantly responsible for increased mortality risk for most categories of deaths, with cumulative relative risk (RR) over 0–27 lagged days of 1.57 [95% confidence interval (CI): 1.48–1.67], 1.95 (1.49–2.55), 1.58 (1.39–1.79), 1.54 (1.26–1.88), 1.92 (1.15–3.22), 1.75, (1.14–2.68), 2.02 (0.78–5.22), 1.92 (1.49–2.48), 1.48 (1.18–1.85), and 1.18 (1.06–1.30) for non-accidental causes, cardiovascular diseases, respiratory diseases, digestive diseases, nervous system diseases, genitourinary diseases, mental diseases, endocrine diseases, external cause and neoplasms, respectively. The magnitudes of the effects of cold spells on mortality varied remarkably among the 35 subcategories, with the largest cumulative RR of 2.87 (1.72–4.79) estimated for pulmonary heart diseases. The elderly and females were at a higher risk of mortality for most diseases after being exposed to cold spells. Increased mortality from a wide range of diseases was significantly linked with cold spells. Our findings may have important implications for formulating effective preventive strategies and early warning response plans that mitigate the health burden of cold spells.